2008
DOI: 10.2975/31.4.2008.291.295
|View full text |Cite
|
Sign up to set email alerts
|

The Employment Intervention Demonstration Program: Major findings and policy implications.

Abstract: This article summarizes the published results of the Employment Intervention Demonstration Program (EIDP), a federally-funded, multi-site study examining the effectiveness of supported employment programs for 1273 unemployed individuals with psychiatric disabilities in the U.S. Findings confirm the effectiveness of supported employment across different models, program locations, and participant populations. The study's results are discussed in the context of public policies designed to encourage return to work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 15 publications
4
50
0
Order By: Relevance
“…Our results are in accordance with a recent meta-analysis on participants in supported employment programs [50] showing that age and education were not associated with a better occupational functioning in schizophrenia, whereas some authors have identified a correlation between younger age and/or advanced education and better vocational functioning [51][52][53][54][55][56][57]. Second, employment was significantly associated with verbal memory, general psychopathology, and awareness of mental illness.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are in accordance with a recent meta-analysis on participants in supported employment programs [50] showing that age and education were not associated with a better occupational functioning in schizophrenia, whereas some authors have identified a correlation between younger age and/or advanced education and better vocational functioning [51][52][53][54][55][56][57]. Second, employment was significantly associated with verbal memory, general psychopathology, and awareness of mental illness.…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, some researchers suggest that vocational rehabilitation should support clients' completion of secondary and post-secondary education (Burke-Miller et al 2006). Employment History Relatively consistent in the literature is the finding that work history predicts vocational success (Catty et al 2008;Cook et al 2008;Tsang et al 2000). Clients who worked in the past benefited more from SE than clients who had no employment histories (Blitz and Mechanic 2006;Burke-Miller et al 2006;Xie et al 1997).…”
Section: Intrinsic Characteristicsmentioning
confidence: 94%
“…In the IPS SE literature, integration is a key element of treatment fidelity and has been shown to be among the best predictors of employment outcomes change [38]. Data suggesting that other clinical services, service providers, and friends and families can play a key role in supporting or discouraging a return to employment underline the importance of interventions that coordinate closely with other services and communicate with the participant's larger social network [39].…”
Section: What Other Outcomes Beyond Competitive Employment Should Bementioning
confidence: 99%